Keluarga Berencana Dalam Perspektif Hadis - Sari, Dina Novita; Arifin, Tajul (El-Ghiroh : Jurnal Studi Keislaman, 2023)
This research is motivated by the large population in the world which can cause an imbalance because a rapidly growing population can result in a population with poor quality and result in the Earth or the State not providing maximum facilities. However, this program has attracted a lot of controversy in Indonesia because the majority are Muslim and consider this program a refusal of the sustenance given by Allah SWT. The purpose of this study is to find out this program from the perspective of Hadith, where Hadith is used as a source of law in Islam but the purpose of Family Planning is to plan for a sufficient number of children and ensure their survival in a family. This research uses descriptive analytical method and applies a qualitative approach, as well as various relevant references as data sources. Data were collected using literature study techniques and then analyzed using content analysis techniques. The results of this study indicate that family planning in the perspective of hadith is allowed but with clear and strong reasons, some hadith scholars also allow it, some do not allow it for various reasons. Further discussion will be presented in this journal.